2022
DOI: 10.1371/journal.pone.0270230
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Fontan-associated hepatocellular carcinoma

Abstract: Aims The incidence of hepatocellular carcinoma (HCC) in patients with Fontan-associated liver disease (i.e., FALD-HCC) has increased over time. However, the risk factors for HCC development remain unclear. Here, we compared the levels of non-invasive markers to the survival rate of FALD-HCC patients. Methods From 2003 to 2021, 154 patients (66 men, 42.9%) developed liver disease after undergoing Fontan procedures. HCC was diagnosed in 15 (9.7%) (8 men, 53.3%) at a median age of 34 years (range, 21–45 years).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…23 In another study from Japan, the cumulative incidence of HCC at 10, 20, and 30 years post Fontan was 0.8%, 2.9%, and 13.3%, respectively. 7 When compared to other liver diseases, the 20-year cumulative incidence of HCC in Fontan patients is higher than in those with autoimmune hepatitis (2.7%) but lower than in those with alcohol-induced cirrhosis without decompensation (24.8%). 54,55 On the other hand, the incidence of HCC in Fontan is similar to or higher than those with inactive chronic Hepatitis B (0.02-0.2 per 100 person-years) but lower than those with chronic HBV and cirrhosis (2.2-3.7 per 100 person-years) and chronic HCV (1%-8%).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…23 In another study from Japan, the cumulative incidence of HCC at 10, 20, and 30 years post Fontan was 0.8%, 2.9%, and 13.3%, respectively. 7 When compared to other liver diseases, the 20-year cumulative incidence of HCC in Fontan patients is higher than in those with autoimmune hepatitis (2.7%) but lower than in those with alcohol-induced cirrhosis without decompensation (24.8%). 54,55 On the other hand, the incidence of HCC in Fontan is similar to or higher than those with inactive chronic Hepatitis B (0.02-0.2 per 100 person-years) but lower than those with chronic HBV and cirrhosis (2.2-3.7 per 100 person-years) and chronic HCV (1%-8%).…”
Section: Discussionmentioning
confidence: 92%
“…[22][23][24][25] Of the remaining 23 studies, 12 and 13 studies were included in the cirrhosis and HCC cohorts, respectively, with two studies, Wu 2017 and Munsterman 2019, common to both cohorts. 4,[6][7][8][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The included studies in cirrhosis and HCC cohorts are reported in Tables 1 and 2, respectively. No randomised control trials were identified in the literature search.…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective studies have shown a prevalence of HCC of 0.18% to 1.3%. 20,21 In recent single-center study by Kogiso et al, 22 9.7% developed HCC within 20 years after the Fontan procedure. In a larger retrospective review of 1117 Fontan patients, Inuzuka et al 9 found that the incidence of liver fibrosis, FNH-like lesions, liver cirrhosis, and HCC started to increase at 5, 5, 10, and 15 years and reached a cumulative incidence of 27.3%, 8.7%, 13.0%, and 1.0%, respectively, at 20 years after Fontan operation.…”
Section: Pathophysiology and Clinical Features Of Fontan-associated L...mentioning
confidence: 96%